Historical Study Of Sepaktakraw Development In Luwoo Village, Gorontalo Province - Mohamad Daulima; Sulaiman Sulaiman; Setya Rahayu (JUARA : Jurnal Olahraga, 2023)
This study aims to: (1) analyze history, (2) analyze the socio-cultural life of the community, (3) analyze organizational management, and (4) analyze the development of sports achievements in sepak takraw in Luwoo village. The method used is qualitative with a case study approach; the research data sources are community leaders, coaches, and athletes through observation, interviews, and documentation data collection techniques. The results of the study show (1) sepaktakraw in Gorontalo, especially in the village of Luwoo, originated from sepak Lilina. The people of Luwoo village have known sepaktakraw since 1976. Then in the 1980s, a community leader invited and coached young people to play sepaktakraw and founded a sepaktakraw club, (2) Luwoo village cannot be separated from the creation of the first takraw ball in Gorontalo District and has several forms according to its development, (3) the management of management receives government support so that it has facilities that can support achievement. (4) the development of the Luwoo village's sepaktakraw achievements began in 1990, and until now, its development has reached the national and international levels. Therefore, Luwoo village is known as takraw village. Based on the results of the study, it can be concluded that the takraw in Luwoo village has existed since 1976; the life of the people of Luwoo village cannot be separated from the making of takraw balls according to their development. The government supports the management of the organization, and the development of the Luwoo village's sepaktakraw achievements has made a lot of progress.